1981
DOI: 10.1007/bf00427109
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a preferential role of brain serotonin in the mechanisms leading to naloxone-precipitated compulsive jumping in morphine-dependent rats

Abstract: Various drugs acting on brain serotonin or catecholamines were administered concurrently with morphine during the development of dependence or before naloxone-precipitated withdrawal syndrome. Of the various drugs only cyproheptadine, a serotonin antagonist, and piribedil, a dopamine agonist, reduced the frequency of jumping (but not of diarrhea or ptosis) when administered with morphine during development of dependence. When administered before naloxone, d-fenfluramine, a serotonin releaser, markedly reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…However, several findings have suggested that 5-HT is not responsible for the physical symptoms of withdrawal (Blasig et al, 1976;Silverstone et al, 1993), except for a possible role in jumping behavior (Cervo et al, 1983;Way et al, 1968). For example, it has been shown that serotonergic transmission blockade, either by specific 5-HT lesion (Ho et al, 1972) or a 5-HT antagonist (Cervo et al, 1981;Samanin et al, 1980) along with chronic morphine treatment, reduces the development of jumping behavior during morphine withdrawal. Concerning the role of serotonin in the motivational aspect of morphine withdrawal, there are conflicting data.…”
Section: Introductionmentioning
confidence: 99%
“…However, several findings have suggested that 5-HT is not responsible for the physical symptoms of withdrawal (Blasig et al, 1976;Silverstone et al, 1993), except for a possible role in jumping behavior (Cervo et al, 1983;Way et al, 1968). For example, it has been shown that serotonergic transmission blockade, either by specific 5-HT lesion (Ho et al, 1972) or a 5-HT antagonist (Cervo et al, 1981;Samanin et al, 1980) along with chronic morphine treatment, reduces the development of jumping behavior during morphine withdrawal. Concerning the role of serotonin in the motivational aspect of morphine withdrawal, there are conflicting data.…”
Section: Introductionmentioning
confidence: 99%
“…The present study confirms and extends these findings, showing that forebrain 5-HT may be particularly involved. Although in experiments with 5,7-DHT no distinction can be made between development and expression of jumping in morphine dependent rats, cyproheptadine and methergoline, two 5-HT antagonists (Clineschmidt & Lotti, 1974;Fuxe, Agnati & Everitt, 1975) were recently found to reduce jumping when administered concurrently with morphine during development of dependence (Cervo et al, 1981;Samanin et al, 1980) but had no effect when given immediately before naloxone-precipitated withdrawal (unpublished results). Therefore, reduced development rather than reduced expression of jumping may occur in animals with impairment of 5-HT transmission in the forebrain.…”
Section: Discussionmentioning
confidence: 98%
“…Withdrawal signs within 30 min were recorded, according to a procedure described previously (Cervo et al, 1981). The Assay of5-hydroxytryptamine Some 5,7-DHT-treated animals that had received no morphine were randomly chosen from the experimental groups and killed by decapitation.…”
Section: Induction Of Dependence and Withdrawal Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-nine hospitalized heroin addicts were randomized to 4 groups: (1) placebo; (2) methadone; (3) buspirone 30 mg daily; (4) buspirone 45 mg daily. The double-blind trial started in all patients with a 5-day methadone stabilization period ending with a 30-mg dose.…”
mentioning
confidence: 99%